COVID-19 and hospital management costs: the Italian experience - Emanuela Foglia; Lucrezia Ferrario; Fabrizio Schettini; M. Beatrice Pagani; Martina Dalla Bona; Emanuele Porazzi (BMC Health Services Research, 2022)
Abstract Background This article investigates the hospital costs related to the management of COVID-19 positive patients, requiring a hospitalization (from the positivity confirmation to discharge, including rehabilitation activities). Methods A time-driven activity-based costing analysis, grounding on administrative and accounting flows provided by the management control, was implemented to define costs related to the hospital management of COVID-19 positive patients, according to real-word data, derived from six public Italian Hospitals, in 2020. Results Results reported that the higher the complexity of care, the higher the hospitalization cost per day (low-complexity = €475.86; medium-complexity = €700.20; high-complexity = €1,401.65). Focusing on the entire clinical pathway, the overall resources absorption, with the inclusion of rehabilitation costs, ranged from 6,198.02€ to 32,141.20€, dependent from the patient’s clinical condition. Conclusions Data could represent the baseline cost for COVID-19 hospital management, thus being useful for the further development of proper reimbursement tariffs devoted to hospitalized infected patients.